Policy of the International Institute of Tropical Agriculture (IITA) on Intellectual Property/Assets - International Institute of Tropical Agriculture (CGIAR System Organization, 2012)
The International Institute of Tropical Agriculture (IITA), a member of the Consultative Group on International Agricultural Research (CGIAR) Consortium, aims to enhance the food security, income, and well being of resource-poor people, primarily in the humid and subhumid zones of sub-Saharan Africa (SSA).